2015
DOI: 10.1016/j.bbamcr.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Defective insulin signaling and mitochondrial dynamics in diabetic cardiomyopathy

Abstract: Diabetic cardiomyopathy (DCM) is a common consequence of longstanding type 2 diabetes mellitus (T2DM) and encompasses structural, morphological, functional, and metabolic abnormalities in the heart. Myocardial energy metabolism depends on mitochondria, which must generate sufficient ATP to meet the high energy demands of the myocardium. Dysfunctional mitochondria are involved in the pathophysiology of diabetic heart disease. A large body of evidence implicates myocardial insulin resistance in the pathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 85 publications
1
37
1
Order By: Relevance
“…2A, B). Although no direct link was made between mitochondrial damage and cardiomyocyte insulin resistance in this study, other researchers have suggested that insulin resistance is downstream of mitochondrial dysfunction in models of diabetic cardiomyopathy (68,69).…”
Section: Discussioncontrasting
confidence: 58%
“…2A, B). Although no direct link was made between mitochondrial damage and cardiomyocyte insulin resistance in this study, other researchers have suggested that insulin resistance is downstream of mitochondrial dysfunction in models of diabetic cardiomyopathy (68,69).…”
Section: Discussioncontrasting
confidence: 58%
“…Insulin inhibits FOXO1 activity, thereby maintaining the integrity of the mitochondrial electron transport chain (METC) and the ratio of NAD +/NADH [18] and protecting mitochondrial function. Therefore, insulin and mitochondria are interdependent; mitochondria require insulin for normal function, mitochondria are required for insulin signaling [99], and skeletal structure and function disorders in aging skeletal muscle increase the risk of insulin resistance.…”
Section: Mitochondrial Dysfunction Can Increase the Risk Of Insulin Rmentioning
confidence: 99%
“…In endothelial cells, mitochondrial fission also contributes to the reduction in eNOS-derived NO bioavailability (9), impairment of angiogenesis (10), and induction of apoptosis (11). Furthermore, an increase in mitochondrial fission is associated with the pathogenesis of diabetic cardiomyopathy (12), nephropathy (13), and peripheral neuropathy (14). …”
Section: Introductionmentioning
confidence: 99%